Investigating Brain Network Changes and Their Association With Cognitive Recovery After Traumatic Brain Injury: A Longitudinal Analysis - Moreira da Silva, Nádia; Cowie, Christopher J. A.; Blamire, Andrew M.; Forsyth, Rob; Taylor, Peter Neal (Frontiers in Neurology, 2020)
Traumatic brain injury (TBI) can result in acute cognitive deficits and diffuse axonal injury reflected in white matter brain network alterations which may, or may, not later recover. Our objective is to first characterize the ways in which brain networks change after TBI and second, investigate if those changes are associated with recovery of cognitive deficits. We aim to make initial progress in discerning the relationships between brain network changes, and their (dys)functional correlates. We analyse longitudinally acquired MRI from 23 TBI patients (two time points: 6 days, 12 months post injury) and cross-sectional data from 28 controls to construct white matter brain networks. Cognitive assessment was also performed. Graph theory and regression analysis were applied to identify changed brain network metrics after injury that are associated with subsequent improvements in cognitive function. Sixteen brain network metrics were found to be discriminative of different post-injury phases. Eleven of those explain 90% (adjusted-R2) of the variability observed in cognitive recovery following TBI. Brain network metrics which had a high contribution to the explained variance were found in frontal and temporal cortex, additional to the anterior cingulate cortex. Our preliminary study suggests that network reorganization may be related to recovery of impaired cognitive function in the first year after a TBI.